Voter Confidence and Increased Accessibility: Act Summary of H.R. 550. (Congressional Digest, 2006)
Part of a special issue on voting integrity. An article excerpted from a summary of HR 550, the Voter Confidence and Increased Accessibility Act of 2006. The Voter Confidence and Increased Accessibility Act was intended to restore confidence in the results of elections and in the U.S. electoral process generally. The measure would require that all voting machines generate an actual paper record that voters can examine to assess the accuracy of their votes and that election officials can use to verify votes should a computer error, hacking, or other irregularity occur.